Pengaruh Keterampilan Membaca Karya Ilmiah Populer Terhadap Minat Baca Mahasiswa PBSI UIN Jakarta - Irhamna Irhamna; Rizka Apriana; Mahmudah Fitriyah (Lembaga Pengembangan Kinerja Dosen, 2024)
Reading is one of the elements of language skills that are at the third level, after listening and speaking skills. Along with the times, the development of reading materials published so that people, especially students, have a varied and not monotonous reading reference. This research uses descriptive quantitative method with survey type. Data collection methods in this study using questionnaires, observations and interviews. The data subjects in this study were Indonesian Language and Literature Education (PBSI) students. This research was conducted at the Faculty of Tarbiyah Science (FITK) UIN Jakarta. This study aims to reveal the phenomenon of Indonesian Language and Literature Education Students of the Faculty of Tarbiyah Sciences (FITK) UIN Jakarta in their interest in reading popular scientific works. The results of this study indicate that factors such as atmosphere, time, and the presence of interesting readings affect students' reading interest, and further understanding of reading preferences and habits can provide additional insights regarding the influence of popular scientific reading skills on the reading interest of PBSI UIN Jakarta 3rd semester students.